2008
DOI: 10.1021/nl801661w
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Comet Assay of Amorphous Silica Nanoparticles Detects No Genotoxicity

Abstract: Genotoxicity of commercial colloidal and laboratory-synthesized silica nanoparticles was tested using the single cell gel electrophoresis or Comet assay. By using a carefully developed protocol and careful characterization of the nanoparticle dispersions, Comet assays were performed on 3T3-L1 fibroblasts with 3, 6, and 24 h incubations and 4 or 40 microg/ml of silica nanoparticles. No significant genotoxicity was observed for the nanoparticles tested under the conditions described, and results were independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(127 citation statements)
references
References 16 publications
(34 reference statements)
6
119
2
Order By: Relevance
“…These generally low responses have been shown to be in accordance with other ecotoxicity studies using engineered amorphous silica NPs, where little or no toxicity was observed in the tests employed (Barnes et al 2008;Shapero et al 2011;Van Hoecke et al 2008). Thus, the lack of toxicity observed to date with amorphous silica NPs, suggests that, in the different standard toxicity methods, this could generally be used as a good negative NP control, except in the case of the cytotoxicity assays which themselves are shown not to be suitable to NP testing.…”
Section: Ecotoxicitysupporting
confidence: 89%
See 3 more Smart Citations
“…These generally low responses have been shown to be in accordance with other ecotoxicity studies using engineered amorphous silica NPs, where little or no toxicity was observed in the tests employed (Barnes et al 2008;Shapero et al 2011;Van Hoecke et al 2008). Thus, the lack of toxicity observed to date with amorphous silica NPs, suggests that, in the different standard toxicity methods, this could generally be used as a good negative NP control, except in the case of the cytotoxicity assays which themselves are shown not to be suitable to NP testing.…”
Section: Ecotoxicitysupporting
confidence: 89%
“…Amorphous silica particles, in comparison, are considered to be relatively harmless and are therefore being produced in large quantities for a large number of applications, especially in biomedical applications and the food sector 5 (Wang et al 2006). Thus, particular concern arises about their possible toxicity and a number of studies have already shown both non toxic (Barnes et al 2008) and toxic effects with amorphous silica NPs (Van Hoecke et al 2008), and specifically in the form of pulmonary inflammation upon inhalation (Rosenbruch 1992).…”
Section: > D Magna > T Platyurus > V Fischerimentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the small size of nanoparticles, they can easily pass through the biological barriers and membranes and can cause toxicity at various sites in the body, i.e. genotoxicity, carcinogenic potential and oxidative stress in organelles, mitochondrial stress and cell-wall disruption [105][106][107]. Therefore, the safety and the possible impact of these nanomaterials should not only be considered for the affected population, but should also cover the entire manufacturing and disposal processes [102].…”
Section: Challengesmentioning
confidence: 99%